1997
DOI: 10.1038/nbt1297-1398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of parthenocarpic plants

Abstract: Transgenic tobacco and eggplants expressing the coding region of the iaaM gene from Pseudomonas syringae pv. savastanoi, under the control of the regulatory sequences of the ovule-specific DefH9 gene from Antirrhinum majus, showed parthenocarpic fruit development. Expression of the DefH9-iaaM chimeric transgene occurs during flower development in both tobacco and eggplant. Seedless fruits were produced by emasculated flowers. When pollinated, the parthenocarpic plants produced fruits containing seeds. In eggpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
151
1
22

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(184 citation statements)
references
References 12 publications
7
151
1
22
Order By: Relevance
“…It is well known that pollen produces gibberellins and that application of gibberellins can induce an increase in the content of auxin in the ovaries of unpollinated flowers of the tomato plant, thereby triggering fruit set in the absence of fertilization (Sastry and Muir, 1963;Gorguet et al, 2005). A crucial role for auxin in seedless tomato fruit formation was directly demonstrated by ovule-specific overexpression of bacterial auxin biosynthetic genes, leading to seedless fruit production independent of pollination (Rotino et al, 1997). Furthermore, downregulation of the tomato Aux/IAA transcription factor IAA9 resulted in auxin-hypersensitive tomato plants in which fruit development was triggered before fertilization and independent of pollination, leading to parthenocarpic fruits (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pollen produces gibberellins and that application of gibberellins can induce an increase in the content of auxin in the ovaries of unpollinated flowers of the tomato plant, thereby triggering fruit set in the absence of fertilization (Sastry and Muir, 1963;Gorguet et al, 2005). A crucial role for auxin in seedless tomato fruit formation was directly demonstrated by ovule-specific overexpression of bacterial auxin biosynthetic genes, leading to seedless fruit production independent of pollination (Rotino et al, 1997). Furthermore, downregulation of the tomato Aux/IAA transcription factor IAA9 resulted in auxin-hypersensitive tomato plants in which fruit development was triggered before fertilization and independent of pollination, leading to parthenocarpic fruits (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of parthenocarpic tomato mutants, such as pat, pat2 and pat3/4, in which it was shown that the GA content and/or GA biosynthesis were increased signiWcantly (Mazzucato et al 1998;Fos et al 2000Fos et al , 2001Olimpieri et al 2007). Furthermore, overexpression of the iaaM gene, which encodes an enzyme involved in auxin biosynthesis, also induced parthenocarpic fruit development in tomato and many other species (Rotino et al 1997;Mezzetti et al 2004). Changes in both GA and auxin content were thus associated with parthenocarpic phenotypes.…”
mentioning
confidence: 99%
“…Genetically controlled parthenocarpy has been observed in tomato (Vardy et al, 1989), banana (Qrtiz and Vuylsteke, 1995) and cucumber (Rudich et al, 1977). A transgenic approach has been successfully applied for obtaining parthenocarpic fruits in eggplant and tobacco (Rotino et al, 1997). Parthenocarpy is a highly appreciated trait by consumers and process companies, not only because of easy processing (e.g.…”
Section: Introductionmentioning
confidence: 99%